COMPARING THE EFFICIENCY OF 2% LIDOCAINE AND 4% ARTICAINE AS A LOCAL ANESTHETIC AGENT IN CHILDREN - Nair, Manisha; Jeevanandan, Ganesh; Mohan, Meenakshi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to compare the anesthetic efficiency of conventional 2% lidocaine with 4% articaine when infiltrated in the maxillary arch for pediatric patients during pulp therapy and extraction. Methodology: A randomized control trial was done with 45 children (n=45) of the age group 4–8 years. The children were randomly allotted to two experimental groups. Group A – Children received 2% Lidocaine HCL infilteration both buccally and palatally, Group B – Children received 2% Lidocaine infilteration buccally and Group C – Children received 4% Articaine infilteration baccally as local anesthetic agent. Post treatment, pain assessment was done using visual analog scale. Results: Articaine group had significantly lower pain scores when compared to the lidocaine group. Conclusion: Articaine infiltration can be considered as an effective alternative for the conventional lidocaine infiltration.